2012
DOI: 10.1002/lsm.22071
|View full text |Cite
|
Sign up to set email alerts
|

Skin rejuvenation by microneedle fractional radiofrequency treatment in Asian skin; Clinical and histological analysis

Abstract: Microneedle fractional RF is a safe and effective skin rejuvenation method in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 17 publications
4
87
0
Order By: Relevance
“…Clinical studies have demonstrated that fractional RF has significant photorejuvenation effect on the aged skin . So far, the photorejuvenation effect of fractional RF has mainly focused on the activation of fibroblasts and increased collagen production in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that fractional RF has significant photorejuvenation effect on the aged skin . So far, the photorejuvenation effect of fractional RF has mainly focused on the activation of fibroblasts and increased collagen production in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that treatment of the skin with RF microneedling has a rejuvenating effect . Dermal remodeling after RF microneedling was shown to produce new collagen, elastin, and hyaluronic acid .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that microneedle fractional bipolar RF treatment is effective for the treatment of photoaged Asian faces with darker skin types, and has little risk of postinflammatory hyperpigmentation. The main limitations of this study were the small number of patients and lack of long-term follow-up after the final treatment [8].…”
Section: Scarlet Platformmentioning
confidence: 97%
“…In another study, Seo et al [8] used a microneedle FRF device (Scarlet, Viol Co.) in 25 female patients, evaluating its safety and efficacy for the treatment of skin rejuvenation. In this study, patients received a total of 3 FRF treatments spaced 4 weeks apart.…”
Section: Scarlet Platformmentioning
confidence: 99%